2016
DOI: 10.1007/s11655-016-2525-y
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture points for treating Parkinson’s disease based on animal studies

Abstract: Parkinson's disease (PD) is a well-known neurodegenerative disease caused by dopaminergic cell death in the nigrostriatal pathway. Recent studies have shown that acupuncture can be a potential therapy for the treatment of PD, but it is not clear which acupuncture points (acupoints) play major roles in reliving symptoms of PD. Yanglingquan (GB 34), Zusanli (ST 36), Fengfu (GV 16), Taichong (LR 3), Baihui (GV 20) and Dazhui (GV 14) acupoints have frequently been to investigate the effectiveness and action mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Acupoints play important roles in reliving the symptoms of PD. Yanglingquan (GB 34), Zusanli (ST36), Fengfu (GV16), Taichong (LR 3), Baihui (GV20), and Dazhui (GV14) acupoints have frequently been investigated for the effectiveness for treating PD [33]. In our study, Baihui (GV20) and Sishencong (EX-HN1) were selected as main points.…”
Section: Discussionmentioning
confidence: 99%
“…Acupoints play important roles in reliving the symptoms of PD. Yanglingquan (GB 34), Zusanli (ST36), Fengfu (GV16), Taichong (LR 3), Baihui (GV20), and Dazhui (GV14) acupoints have frequently been investigated for the effectiveness for treating PD [33]. In our study, Baihui (GV20) and Sishencong (EX-HN1) were selected as main points.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is widely used in East Asia and considered an alternative therapy for PD [11], although recent studies have shown that acupuncture treatment has neuroprotective effects and alleviates behavioral dysfunctions in a PD mouse model [12, 13]. And recently, acupuncture has been suggested as a possible therapeutic tool for treatment of neurodegenerative diseases by inducing neurogenesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture at LR-3 can not only reduce depression but also treat some brain diseases [ 30 , 63 ]. ST-36 is used to relieve pain, numbness, and dysfunctions of the digestive system, restricted movement, and to strengthen the entire body [ 27 ]. Our study focused on the NMS of Parkinson’s disease, including depression, gastrointestinal dysfunction, et al This complex disease requires the joint application of multiple acupoints, and the selection of these four acupoints is also in line with the clinical practice of traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%